ENVIRONMETAL IMPACTS WHEN BUILDING AN ELECTRICAL SUBSTATION IN WISCONSIN POWER AND LIGHT TERRITORY - Barahona, Michael (My University, 2011)
This research states the importance of electrical substations to meet the increasing electrical demands in rural areas taking as an example Wisconsin Power & Light (WP&L) territory. Given the fact that WP&L is a regulated company; the substation is design, construct and operate to meet their customer?s needs at the lowest possible cost without jeopardizing safety or reliability. Therefore, the general design considerations are identified and described in this report. Some of the general considerations includes: site location, environmental, interfacing with other utilities (i.e. telecommunications), reliability, operating, safety and maintenance. In addition, many engineers with varying backgrounds are engaged in the analysis, design, and construction of electrical substation; however, it seems that the most difficult part of constructing one is getting the necessary permits for erosion and sediment control or stormwater management. For this reason, this research will serve as a guide to engineers to understand what the documents are required to get permits. With this in mind, this research focuses on the permitting and environmental issues that are encountered in the construction of an electrical substation. It describes the necessary permits, zoning and ordinances restrictions, long-term impacts and impacts during construction such as runoff and stream pollution. A compilation of requirements was gathered throughout WP&L territory and analyzed. Recommendations are provided to meet them by either using an erosion control and/or storm water plan using the best management practices.